Evaluation of the Completeness and Timeliness of the Infant Pertussis Surveillance System in the Czech Republic in 2015, 2017 and 2019 - LIPTÁKOVÁ Monika; ŠPAČKOVÁ Michaela; BALASEGARAM Sooria; MALÝ Marek; KYNČL Jan; FABIÁNOVÁ Kateřina (Sciendo, 2023)
The completeness and timeliness of the pertussis questionnaire-based enhanced surveillance system (ESS) among infants and reported pertussis data within the electronic nationwide notification system (NNS) in the years 2015, 2017 and 2019 were evaluated in a pilot study.